Opportunities of the National Anti-Corruption Bureau of Ukraine to investigate cases prosecuted by the Prosecutor's Office: from the history of the issue to normative proposals - Derkach, Serhii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is dedicated to the analysis of the theoretical preconditions and normative regulation of the possibility of the National Anti-corruption Bureau of Ukraine to carry out pre-trial investigation in cases that were previously held by other investigative bodies, in particular the prosecutor’s offices.